Analysis of antibiotic costs for inpatients with urinary tract infection at hospital X in Kediri - Muhammad Saddam Albiansyah Tohari; Anggi Restyana; Hanie Kusuma Wardani; Fidi Setyawan (Universitas STRADA Indonesia, 2025)
Urinary Tract Infection (UTI) is a condition where germs grow and reproduce in the urinary tract with significant amounts of bacteriuria. UTIs are treated with antibiotics. Standardization of treatment considers more effective drugs at lower costs to reduce the number of events and health costs. The aim of this research is to determine the cost-effectiveness of using antibiotics in UTI patients at the Hospital in Kediri City, to identify the most cost-effective alternatives to achieve predetermined goals or criteria that cannot be measured in monetary terms, for example several health outcomes. The study was conducted using a retrospective method that compared the direct medical cost of antibiotics for UTI patients. The population of this study was all 44 inpatient UTI patients at the Hospital X in Kediri. The data were analyzed by calculating the Average Cost Effectiveness Ratio (ACER) and Incremental Cost Effectiveness Ratio (ICER). The results of the research showed that the average total cost effectiveness of the antibiotic Levofloxacin was lower by IDR. 2.448.854 compared to ceftriaxone with an average cost of Rp. 2.474.673. The effectiveness of the antibiotic Levofloxacin is more cost effective than Ceftriaxone because it has a lower ACER value, namely Rp. 594.382.039. The calculated ICER value for both antibiotics is Rp. -58.679.55. The conclusion in this study is that to achieve cost effectiveness of a treatment, an ICER value is needed and the calculation was obtained at Rp. -58.679.55. This shows that there is a cost reduction of Rp. -58.679.55 in the use of the antibiotic Ceftriaxone to obtain lower cost effective results